PERCEPTUAL MAPPING POTENSI EKONOMI MAKANAN TRADISIONAL SEBAGAI PANGAN FUNGSIONAL BERBASIS PANGAN LOKAL KOTA SURAKARTA - Utami Tri Sulistyorini; Jusmi Amid; Sri Widiyati; Nurseto Adhi (Politeknik Negeri Semarang, 2019)
This research is based on previous research’s result that there was a image changing of Surakarta City from Batik’s City toward City of traditional Food. There are four objectives of this research, those are; (1) identify Surakarta traditional food’s as functional foods; (2) Mapping the growth of Surakarta’s traditional foods at least five periode; (3) mapping the potential of Surakarta’s traditional foods as a culture heritage’s foods, functional food dan popular foods. (4) mapping the economic potential of Surakarta’s tradisional foods. The objective of this research will be achieved toward analysis primary and secondary datas. Primary datas are obtained by survey method with 200 respondents and analyzed by using BiPlot, Pearson Correlation and Descriptive method. Sencondary datas are obtained from BPS, and Disperindag, and analyzed by using linier regression dan Pearson Correlation.This researh results that the eight of Surakarta’s traditional foods are culture inheritage’s foods, functional foods, favorite foods and have economic potential to rise t Surakarta’s economy growth. Therefore if the Surakarta’s region government should employ three stages to develope these traditional foods as their food city branding. There are clustering analysis, SAP analysis and developing trust (social capital) toward their food city branding.